Taking back control recontextualizing the epicurean maxim lathe biosas in the rise of social media (Lagom: Compendium of CAS Undergraduate Research Abstracts, 2021)
Social media has been perceived as a great force that incessantly takes people's time and attention due to its irresistible nature and strong cultural forces attached to it. This thesis aims to look into the problem of social media overuse and seeks to recontextualize the Epicurean maxim Lathe Biosas as an approach to social media use that renders time on a limited number of well-chosen and curated ventures and optimized practices. It directs one to benefit from the functions of social media and focus on the attainment of pleasure and tranquility while voluntarily forgoing all unnecessary endeavors in social media that decrease happiness and quietude of an individual.